Analisis Pengaruh Unsur Pemadu Terhadap Struktur Mikro Dan Kekerasan Pada Baja Laterit - Eko Sulistyo; Jumadi Jumadi (JURNAL POWERPLANT, 2016)
Analysis of the influence of alloying elements on the composition of the appointment in the womb does not spread evenly on the steel samples of laterite, this is possible because the steel sample ketebalanpadadaerah laterite. At the micro structure of steel material hasilnyaadalahdaerah laterite classified as low, medium, high and this is caused because the carbon content in the area of ​​steel material laterite percent lower alloying element content. Results microscopy analysis on steel samples of laterite by viewing the crystal grains with pembesaranmasing each 50 μm and 30 μm, showed the homogeneity of grains spread evenly. Basically the results of the domestic industry has been quite satisfactory in the quality control process pembuatannya.Namun seen in the test object lateritbentuk steel microstructure in the steel material lateritkurang evenly. In the test of the strength of the metal material has an advantage in the Brinell hardness test.